Exploring the RNase A scaffold to combine catalytic and antimicrobial activities. Structural characterization of RNase 3/1 chimeras - Fernández-Millán, Pablo; Vázquez-Monteagudo, Sergi; Boix, Ester; Prats-Ejarque, Guillem (Frontiers in Molecular Biosciences, 2022)
Design of novel antibiotics to fight antimicrobial resistance is one of the first global health priorities. Novel protein-based strategies come out as alternative therapies. Based on the structure- function knowledge of the RNase A superfamily we have engineered a chimera that combines RNase 1 highest catalytic activity with RNase 3 unique antipathogen properties. A first construct (RNase 3/1-v1) was successfully designed with a catalytic activity 40-fold higher than RNase 3, but alas in detriment of its anti-pathogenic activity (Prats-Ejarque et al., 2019a). Next, two new versions of the original chimeric protein were created showing improvement in the antimicrobial activity (Prats-Ejarque et al., 2021). Both 2nd generation versions (RNases 3/1-v2 and -v3) incorporated a loop characteristic of RNase 3 (L7), associated to antimicrobial activity. Last, removal of an RNase 1 flexible loop (L1) in the 3rd version enhanced its antimicrobial properties and catalytic efficiency. Here we solved the 3D structures of the three chimeras at atomic resolution by X-ray crystallography. Structural analysis outlined the key functional regions. Prediction by molecular docking of the protein chimera in complex with dinucleotides highlighted the contribution of the C-terminal region to shape the substrate binding cavity and determine the base selectivity and catalytic efficiency. Nonetheless, the structures that incorporated the key features related to RNase 3 antimicrobial activity retained the overall RNase 1 active site conformation together with the key structural elements for binding to the human ribonuclease inhibitor (RNHI), ensuring non-cytotoxicity. Results will guide us in the design of the best RNase pharmacophore for anti-infective therapies.